(untitled) (Fiep Bulletin - online, 2016)
Obesity and overweight come significantly increasing worldwide in recent years. With technological advances in recent decades, the school became less physically active, which contributed to the increase in overweight and obesity in these groups. It was held a direct descriptive field research with a quantitative approach in order to collect data to determine the prevalence of obesity in schoolchildren that attend to physical education classes of high school at the Municipal School Manoel Bastos Ribeiro in the city of Itaueira-Piaui . The sample by convenience comprised 64 students above 18 years old from the 3rd year of high school. Obesity and overweight were evaluated by body mass index (BMI) and classification was performed according to WHO table having BMI the following parameters: <18.5 Underweight; between 18.5 and 24.9 normal weight; between 25.0 and 29.9 overweight; between 30.0 and 34.9 obesity. During collection, a lecture was held to clarify the procedures to be adopted in the research. Anthropometric measurement standards had to be followed. It was found that about 17% of schoolchildren are overweight and 11% of them are obese. It is also noted that the prevalence of obesity is higher among students who do not attend the Physical Education classes (33%) compared to the students that attend to physical education classes (2%).